Strategi Promosi Wisata di Deli Serdang saat Pandemi Covid-19 oleh Dinas Kebudayaan Pemuda dan Olahraga - Zega, Taslim Anwar; Batubara, Beby Mashito; Barus, Rehia K Isabella (Universitas Medan Area, 2024)
During the Corona Virus Disease 2019 (COVID 19) pandemic, it resulted in a decrease in tourist visits to tourist objects. For this reason, the Department of Culture, Youth and Sports and Tourism of the Deli Serdang district needs to carry out a strategy to increase the promotion of tourist attractions. Covid 19 pandemic in Deli Serdang Regency. The research method used is descriptive qualitative. Data collection techniques using interviews, observation, and documentation. The results showed that the strategy used was the theory according to Peter and Olson, including advertising, sales promotion, personal selling and publicity. Sales promotion strategies such as direct promotion by tourist attraction managers, advertisements such as promotional exhibitions using social media and publicity such as introducing virtual exhibitions and so on. The inhibiting factors for the strategy in increasing promotion include the status of the Covid 19 pandemic which has not yet ended and the lack of a budget.